Linking ability-enhancing HR practices, customer satisfaction and emotional intelligence: insight from the banking sector. (13th August 2019) - Azhar, Sarah; Naqvi, Syed M. Imran Haider; Rashid, Muhammad Amir; Imran, Asma
This study defines and expounds the relationship between ability-enhancing HR practices (A-HRM) and customer satisfaction (CS). Ability-enhancing HR practices comprise recruitment and selection (R&S) and training (TR). The mediating role of emotional intelligence (EI) is tested within the relationship of A-HRM and CS. The study was conducted on a group of 467 employees and same number of customers from 126 bank branches operating in Punjab, Pakistan. Structural equation modelling (SEM) was used in the process of statistical analysis. The research confirmed a significant statistical relationship between all studied variables: A-HRM, EI and CS. It was concluded, on the basis of the analysis, using SEM, that AHRM has an indirect influence on CS, through EI. A cross-sectional design and use of self-reported questionnaire data are limitations of this study. This study theoretically confirms that emotional intelligence has a positive impact on customer satisfaction and a mediating effect on the relationship between ability-enhancing HR practices and customer satisfaction. The results of this research extend the knowledge in the area of customer service outcomes, with reference to HR practices and emotional intelligence in the organisations.